Analisis Peran Kepala Desa Dalam Perencanaan Pembangunan Di Desa Nen Bura - Amandus, Mikelson (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
The progress of a village cannot be separated from the role of the village head and his community through local government and central government programs aimed at advancing the village for the benefit of the community and the village itself. This research aims to determine the role of the village head in development planning in Nen Bura village. This study utilizes qualitative research methods. The results of this study indicate that in general the role of the Village Head in government affairs, the development planning process in Nen Bura Village is running quite well even though it has not yet achieved optimal results. Optimizing the role of the Village Head in the village development planning process is very much needed in order to be able to realize unfinished development